Some wood properties of Pinus patula (Schiede and deppe) from Uganda and techniques developed in studying them - Plumptre, R (Department of Forestry, Commenwealth Forestry Institute, University of Oxford, 1978)
A comparison is made of 25 physical and mechanical properties of the wood of Pinus patula(Schiede and Deppe) from twenty trees from four sites in Uganda. X-ray densitometry was used to study wood density and statistical methods were used to analyse the data; a number of techniques were developed to study particular properties. The following were the main findings of the study. The range of physical and strength properties between and within trees was determined. Between site differences were small compared with between tree differences; within tree differences followed the normal increase of density and strength from pith to bark but were more variable up the tree. The limited number of morphological characters studied were not closely related to wood properties. Principal component and regression analysis showed strength properties (except cleavage strength) and density to be closely related. Shrinkage and distortion were not closely related to other properties except grain angle. A contour drawing program for maps was adopted and used to compare contours of density, ring width and 'dry matter' production within trees. This enabled the effects of rate of growth on wood density and total wood production to be seen within different parts of the stem of the tree avoiding the confusions of physiological and chronological age inherent in most mathematical methods of analysis. The technique is not, however, easily susceptible to testing for statistical reliability. There appeared to be a close relationship between ring width and wood density within an individual tree. Variations in size of juvenile core and differences between the core and mature wood were considerable. Transition from core to mature wood was found to be sharp where a severe pruning had occurred. A computer program was developed to integrate wood density, wood volume and weight of wood produced during the whole of each year's growth of wood in order to measure the total, averaged, response of the tree to environment and silvicultural treatments. Although the number of trees was small the study suggested a close relationship between pruning and wood density and that it may be possible to control juvenile core by pruning without seriously reducing volume production. In spite of variation of density patterns between trees, fairly close correlations were obtained between breast height wood density in the early life of the tree and whole tree wood density at 20 years old; breast height cores taken from 5 year old trees appear to give a good indication of what future wood density will be and which trees are likely to be superior in this respect. In spite of the generally good relationship between wood density and the main strength properties, consistent differences in specific strength (strength:weight ratio) were found between different trees, suggesting that some trees may produce more efficient wood in terms of strength per unit of weight than others. No attempt was made in this study to discover the reasons for this. A number of suggestions are made for further study.